2021
DOI: 10.1016/j.psj.2020.10.065
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial transcription factor A induces the declined mitochondrial biogenesis correlative with depigmentation of brown eggshell in aged laying hens

Abstract: Eggshell color is an important characteristic for poultry eggs. Eggs from aged hens usually have poor shell color that is unacceptable for the table egg market. The objective of this study was to examine effects of pigment synthesis and mitochondrial biogenesis on brown eggshell color of aged laying hens. In this trial, 8 hens laying eggs with darker shell color and 8 hens laying eggs with lighter shell color were selected from 300 62-week-old Hy-Line brown-egg laying hens. Results showed that egg weight ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…The subject of whether eggshell color affects eggshell quality has attracted the interest of researchers. In our study, there were no significant differences between LBS and DBS lines in terms of eggshell thickness and eggshell proportion, which is consistent with previous research findings [ 23 , 26 ]. However, the eggshell strength of DBS line eggs was significantly weaker than that of LBS line eggs, which may be attributed to the influence of eggshell pigment on the eggshell calcification process.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The subject of whether eggshell color affects eggshell quality has attracted the interest of researchers. In our study, there were no significant differences between LBS and DBS lines in terms of eggshell thickness and eggshell proportion, which is consistent with previous research findings [ 23 , 26 ]. However, the eggshell strength of DBS line eggs was significantly weaker than that of LBS line eggs, which may be attributed to the influence of eggshell pigment on the eggshell calcification process.…”
Section: Discussionsupporting
confidence: 93%
“…Numerous studies have shown that eggshell brownness is regulated by synthases and transporters in the Pp IX/heme synthesis pathway. ALAS1 is the target gene for the regulation of Pp IX concentration in eggshells [ 19 , 23 ]. ABCG2 has been shown to regulate ALA-mediated Pp IX levels by exporting Pp IX from the mitochondria to the cytoplasm [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…ABCG2 is responsible for the export of protoporphyrin out of cells ( Ajioka et al, 2006 ), and identified as a causative gene for blue eggs in the duck ( Chen et al, 2020 ). These genes had higher expression levels in the dark brown-shell chickens than the light brown-shelled ones ( Li et al, 2013 ; Zheng et al, 2014 ; Lu et al, 2021a ). ALAS1 was confirmed to be the key gene reducing protoporphyrin biosynthesis in response to nicarbazin treatment ( Samiullah et al, 2017 ).…”
Section: Introductionmentioning
confidence: 94%
“…Freckles are more likely to appear on brown-shelled eggs than on eggshells of other colors. Brown eggs are mainly composed of pigments such as protoporphyrin IX [ 9 ]. Currently, there are two prevailing views on the manner in which the site of pigment synthesis occurs in brown eggs: one view is that the pigment is synthesized by red blood cells in the circulatory system [ 10 ]; the other view is that the pigment is synthesized by epithelial cells in the uterus [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%